Mechanically Stable Dynamic Urea Bond‐Based Crosslinked Polymer Blend with Tunable Self‐Healable and Physical Properties. Issue 1 (9th November 2020) - Zhou, Zhongqun; Chen, Shenye; Li, Weichen; He, Junjie; Yu, Caili; Zhang, Faai
Abstract: Polymer networks crosslinked by reversible noncovalent crosslinks have been applied in self‐healing and recyclable sustainable materials but result in limited mechanical strength. Herein, a crosslinked polymer blend that is based on a urethane–arcylate system with a combination of reversibly noncovalent intrachain and interchain hydrogen bonds and dynamically covalent urea bonds is developed through facile in situ photo‐induced copolymerization. An essential step is the introduction of a flexibly dynamic crosslinker bearing robustly hindered urea bonds and urethane–urea structures into the network, which endows the dynamic network with a synergy of mechanical robustness and desirable self‐healing ability. The dynamic networks exhibit rapid self‐healing at mild conditions (70 °C, 30 min), extreme toughness (≈34.76 MJ m −3 ), high tensile strength (≈7.78 MPa), superior stretchability (≈932%), long‐term stability, recyclability, and weldability. More importantly, the mechanical and self‐healing properties of the resultant materials can be fine‐tuned by adjusting the dynamic crosslinker content. These superior properties are attributed to the dynamic reversibility of hydrogen bonds and urea bonds as monitored by rheological tests. The extremely facile fabrication approach and superior properties of the resulting self‐healing polymers can find applications in sustainable smart materials and self‐healing conductive sensors. Abstract : A crosslinked polymer blend based on a urethane–arcylate system with a combination of reversibly noncovalent intrachain and interchain hydrogen bonds and dynamically covalent urea bonds is developed through a facile in situ photo‐induced copolymerization. The materials exhibit rapid self‐healing at mild conditions (70 °C, 30 min), extreme toughness (≈34.76 MJ m −3 ), high tensile strength, superior stretchability, long‐term stability, recyclability, and weldability.